2013
DOI: 10.1111/bjso.12029
|View full text |Cite
|
Sign up to set email alerts
|

Is everyone Irish on St Patrick's Day? Divergent expectations and experiences of collective self‐objectification at a multicultural parade

Abstract: We examine experiences of collective self‐objectification (CSO) (or its failure) among participants in a ‘multicultural’ St Patrick's Day parade. A two‐stage interview study was carried out in which 10 parade participants (five each from ethnic majority and minority groups) were interviewed before and after the event. In pre‐event interviews, all participants understood the parade as an opportunity to enact social identities, but differed in the category definitions and relations they saw as relevant. Members … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 33 publications
2
25
0
Order By: Relevance
“…Furthermore, our findings extend the argument that identity consolidation can provide the means for gaining influence as a protest movement (see Kinder, ; Turner, ) to beliefs about the efficacy of collective action. Our work also extends research on empowerment in collective action (Drury & Reicher, ; Drury et al ., ; Pehrson et al ., ) by (1) showing that previously identified antecedents of empowerment might be usefully viewed through the broader lens of identity consolidation and (2) providing indirect quantitative evidence suggesting that anticipated empowerment through collective action may be closely linked to anticipated identity consolidation through collective action.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, our findings extend the argument that identity consolidation can provide the means for gaining influence as a protest movement (see Kinder, ; Turner, ) to beliefs about the efficacy of collective action. Our work also extends research on empowerment in collective action (Drury & Reicher, ; Drury et al ., ; Pehrson et al ., ) by (1) showing that previously identified antecedents of empowerment might be usefully viewed through the broader lens of identity consolidation and (2) providing indirect quantitative evidence suggesting that anticipated empowerment through collective action may be closely linked to anticipated identity consolidation through collective action.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the potential of collective action to consolidate the identity of the protesting group encompasses Hornsey et al's (2006) efficacy at expressing values, building an oppositional movement, and influencing public opinion (to which we add showing support for the disadvantaged group). The idea that prior to participation, people think about the potential of collective action to achieve some form of identity consolidation, is well illustrated in research by Pehrson, Stevenson, Multoon, and Reicher (2013). The authors interviewed participants in a St Patrick's parade in Ireland and found differences in their expectations of the event's potential to help them enact their own understandings of the Irish identity.…”
mentioning
confidence: 99%
“…Also, some events may be more contested than others (giving rise to factionalism). Moreover, some participants may find their presence questioned such that although they identify with others they may feel marginalized and unable to enact their identification (Pehrson, Stevenson, Muldoon, & Reicher, ). Such experiences may reduce the extent of CSR and hence participants' postevent identification strength (and when interpreting our own data, it is appropriate to note that an overall increase in the Kalpwasis' identification strength does not necessarily mean everyone increased their identification).…”
Section: Discussionmentioning
confidence: 99%
“…The identity motive literature assumes that various identity motives "push for certain ways of seeing oneself" (Vignoles, 2011, p. 406) and that the satisfaction of these motives drives particular forms of behaviour and identification. It is one thing for the subject to self-define and claim a particular identity, but the process is incomplete without others accepting that claim (Hopkins & Greenwood, 2013;Pehrson et al, 2014). As much social anthropological (e.g., Barth, 1969) and sociological (e.g., Goffman, 1969) theory argues, if we are to speak of a person as "having an identity" it is important that others recognise and orient to that person as having that identity (Jenkins, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Just because people are in close proximity does not mean that they think of themselves as a group. Furthermore, although there may be some in the crowd who identify with others, this may not be reciprocated such that any sense of a shared identity is unsustainable (Pehrson, Stevenson, Muldoon, & Reicher, 2014). Some mass gatherings are riven by tension as different factions contest the meaning of the event (Coleman, 2002;Eade & Sallnow, 1991;Sallnow, 1981) and even where a shared identity is possible, participants may differ in the degree to which they identify with others (Alnabulsi & Drury, 2014;Khan et al, 2015Khan et al, , 2016.…”
mentioning
confidence: 99%